Visual arts and remote education: : paroxism in interactions in pandemic times (Palíndromo, 2021)
The article reflects on the Teaching of Visual Arts in a remote and pandemic context, from the incidence of instabilities, transformations and challenges in the teaching work, in which the school space is moved to the spaces of the homes of students and teachers. It is possible to observe the importance of bonds of trust in the family-school relationship, and of teachers as indispensable characters in this challenging context, where the arts together with educational practices suggest forms of [re] knowledge and social transformation in the midst of cyberculture.
Keywords: Cyberculture; Visual Arts Teaching.; Remote Teaching.